Evolution of Media Supporting the Development of Mammalian Preimplantation Embryos In Vitro - Hongsheng Men (Biology)
Assisted reproductive technology has revolutionized our ability to genetically manipulate, maintain and rederive laboratory animals of biomedical importance; manipulate animal reproduction or genetics to boost production of farm animals; and improve human reproductive health. The media for in vitro manipulation and the culture of embryos play a critical role in the development of assisted reproductive technology. In this review, the evolution of culture media supporting embryo development in vitro from selected animal species, laboratory animals (mice and rats) and farm animals (pigs and cattle), will be discussed with a focus on the development of chemically defined media.